The Economic Issues of Compulsory Health Insurance: Comment - Falk, I. S. (Quarterly Journal of Economics, 1952)
Journal Article The Economic Issues of Compulsory Health Insurance: Comment Get access I. S. Falk I. S. Falk Social Security Administration, Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 4, November 1952, Pages 572–586, https://doi.org/10.2307/1882106 Published: 01 November 1952